Qiliqiangxin Capsule Modulates Calcium Transients and Calcium Sparks in Human Induced Pluripotent Stem Cell-Derived Cardiomyocytes. (30th August 2022) - Li, Yuxin; Zhang, Zhang; Hao, Xuezeng; Yu, Tingting; Li, Sen
Abstract : Background . The therapeutic effects of Qiliqiangxin capsule (QLQX), a Chinese patent medicine, in patients with chronic heart failure are well established. However, whether QLQX modulates cardiac calcium (Ca 2+ ) signals, which are crucial for the heart function, remains unclear. Aim of the Study . This study aimed to evaluate the role of QLQX in modulating Ca 2+ signals in human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs). Materials and Methods . Fluorescence imaging was used to monitor Ca 2+ signals in the cytosol and nuclei of hiPSC-CMs. For Ca 2+ spark measurements, the line-scan mode of a confocal microscope was used. Results . The QLQX treatment substantially decreased the frequency of spontaneous Ca 2+ transients, whereas the amplitude of Ca 2+ transients elicited by electrical stimulation did not change. QLQX increased the Ca 2+ spark frequency in both the cytosol and nuclei without changing the sarcoplasmic reticulum Ca 2+ content. Interestingly, QLQX ameliorated abnormal Ca 2+ transients in CMs differentiated from hiPSCs derived from patients with long-QT syndrome. Conclusions . Our findings provide the first line of evidence that QLQX directly modulates cardiac Ca 2+ signals in a human cardiomyocyte model.